Criticism of Phonetic Terms Related to Sound Articulation in Modern Arabic Linguistics - Mohammed, Zainab Bassem; Hassan, Mohamed Bashir (Journal of Ecohumanism, 2024)
The research is interested in tracking the idea of ​​criticizing the phonetic term in linguistic research, as it became clear that there is a scientific activity focused on criticizing the phonetic term, and this criticism was within the framework of a problem related to the chaos of the modern phonetic term that was affected by the data of the era, including translation, modernity, and the interaction of sciences and what it left behind on the phonetic level, in addition to the novelty of the topics that were studied, issues related to and touching on the reality of usage, which created terms that may be accurate or inaccurate according to the vision of modern linguists. It was therefore important to study this intellectual activity and shed light on it through research and investigation.